Intelligent Interface for Knowledge Based System - Nyoman Bogi Aditya Karna; Iping Supriana; Ulfa Maulidevi (Universitas Ahmad Dahlan, 2014)
Every Knowledge Based System has their own knowledge formalism depends on the problem to be solved, goal to be achieved, and proposed solution. This means every knowledge contained in the system will differ from one system to another. This was also meant that this knowledge cannot be used by other system, which in return makes every system must start with a learning phase from the start. One of the solutions to overcome this problem is by providing a unified model that can accept all type of knowledge which guarantees automatic interaction between Knowledge Based System. Interaction in this paper is defined as knowledge sharing, integration, and transfer from one system to another. This research provides the model and conducts the test on interaction capability. This research contributes for accelerating a new Knowledge Based System establishment because it does not need a knowledge initialization.